Development of Learning Videos to Improve Students' Ability to Understand Mathematical Concepts on Polynomial Material - Paulus Nainggolan; Bornok Sinaga (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
Behind the success of successful online teaching and learning, there must be careful preparation in creating or building the system. Some complaints that are around us are that some students have difficulty in online-based mathematics learning. Some of them have difficulty signaling due to cloudy or rainy weather, not having money to buy internet quota, boredom during the teaching, and learning process, and difficulty understanding the material in online learning. Although there are examples that have been explained by the teacher, they still do not understand what their teacher teaches them. The teacher had already made learning materials using instructional video media, but it was still not enough for students to understand the polynomial material taught by the teacher, and according to the teacher the main problem was that the students' ability to memorize formulas was still lacking. The objectives of this research to see validity, effectiveness and practicality of the video development using PowerPoint and Filmora application. This research is development research that applies the Dick & Carey development model. This research focuses on developing learning videos using PowerPoint as a learning media, and Filmora as a learning video editing medium.